Urban Poverty and Transport : The Case of Mumbai - Baker, Judy (World Bank, Washington, DC, 2012)
This paper reports the results of a survey of 5,000 households in the Greater Mumbai Region conducted in the winter of 2004. The goal of the survey was to better understand the demand for transport services by the poor, the factors affecting this demand, and the inter-linkages between transport decisions and other vital decisions such as where to live and work. This paper, the first of several research outputs, describes the salient facts about travel patterns in Mumbai for both poor and non-poor households. A striking finding of the survey is the extent to which all households-especially poor households-rely on walking. Overall, 44 percent of commuters in Mumbai walk to work. The proportion of the poor who walk to work is even higher-63 percent. Walking is an even higher modal share for nonwork than for work trips. A second finding is that public transit remains an important factor in the mobility of the poor, and especially in the mobility of the middle class. Overall, rail remains the main mode to work for 23 percent of commuters, while bus remains the main mode for 16 percent of commuters. The modal shares for bus are highest for the poor in zones 1-3 (21 percent of the poor in zone 2 take the bus to work), while rail shares are highest for the poor in the suburbs (25 percent of the poor in zone 6 take rail to work). Is the cost and lack of accessibility to transit a barrier to the mobility of the poor? Does it keep them from obtaining better housing and better jobs? This is a difficult question to answer without further analysis of the survey data. But it appears that transport is less of a barrier to the poor who live in central Mumbai (zones 1-3) than it is to the poor who live in the suburbs (zones 4-6). The poor who live in zones 1-3 (central Mumbai) live closer to the non-poor than do poor households in the suburbs. They also live closer to higher-paying jobs for unskilled workers. Workers in these households, on average, commute short distances (less than 3 kilometers), although a non-negligible fraction of them (one-third in zone 2) take public transit to work. It is true that the cost of housing for the poor is higher in central Mumbai than in the suburbs, but the quality of slum housing is at least as good in central Mumbai as in the suburbs. The poor who live in the suburbs of Mumbai, especially in zones 5 and 6, are more isolated from the rich than the poor in central Mumbai: 37 percent of the poor live in zones 5 and 6, whereas only one-fifth of higher income groups do. Wages for skilled and unskilled labor are generally lower in zones 5 and 6 than in the central city, and it appears that unemployment rates for poor males are also higher in these zones. The lower cost of slum and chawl housing in zones 5 and 6 may partly compensate for lower wages. However, a larger proportion of workers in poor households leave zones 5 and 6 to work than is true for poor workers in other zones. Commuting distances are much higher for poor workers in the suburbs than for poor workers in zones 1-3.